CAREDAS: a Comprehensive Architecture for a Redundant and Evolutive Data Acquisition System for JHR reactor - Leroux Fabrice (EDP Sciences, 2021)
A new material testing reactor Jules Horowitz Reactor is under construction at CEA Cadarache. The materials to be irradiated will be placed into experimental devices around the reactor. Process and measurements of experimental devices will be carried out by command control. A data acquisition system having processing performances will be associated to the programmable logic controller. The challenge is to design and realize for twenty experiment devices a high availability data acquisition system architecture for 50 years of sustainability. The real time target will achieve 24/7 data acquisition and real time processing. This scalable architecture could be use as well for JHR experimental devices with high availability as for testbed. This architecture could be run on a standalone station for a measuring bench or deployed on cluster for high availability. CAREDAS’s design is modular and use proven widely used open source solutions. All parts are independent from each other and can be replaced with another technology with the same functionalities. This ensures sustainability and control of software sources.